2010
DOI: 10.1051/0004-6361/201014559
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the ionised gas around the luminous QSO HE 1029-1401: evidence for minor merger events?

Abstract: We present VIMOS integral field spectroscopy of the brightest radio-quiet QSO on the southern sky HE 1029-1401 at a redshift of z = 0.086. Standard decomposition techniques for broad-band imaging are extended to integral field data in order to deblend the QSO and host emission. We perform a tentative analysis of the stellar continuum, finding a young stellar population (<100 Myr) or a featureless continuum embedded in an old stellar population (10 Gyr) typical for a massive elliptical galaxy. The stellar veloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 105 publications
4
23
1
Order By: Relevance
“…Based on the velocity structure and mass of EELR gas around SSRQs, as well as the correlation between EELRs and radio emission, Fu & Stockton (2009) suggested that EELRs are formed in galaxy minor mergers accompanied by the production of radio jets associated with AGNs. A similar conclusion was reached by Husemann et al (2010) for an RQQ. Villar-Martín et al (2011) found that the majority of the type-2, radio-quiet EELR quasars show the signs of galaxy merger or interaction, while none of the non-EELR counterparts show such signs.…”
Section: Link To Host Galaxiessupporting
confidence: 79%
See 1 more Smart Citation
“…Based on the velocity structure and mass of EELR gas around SSRQs, as well as the correlation between EELRs and radio emission, Fu & Stockton (2009) suggested that EELRs are formed in galaxy minor mergers accompanied by the production of radio jets associated with AGNs. A similar conclusion was reached by Husemann et al (2010) for an RQQ. Villar-Martín et al (2011) found that the majority of the type-2, radio-quiet EELR quasars show the signs of galaxy merger or interaction, while none of the non-EELR counterparts show such signs.…”
Section: Link To Host Galaxiessupporting
confidence: 79%
“…We compile the EELR measurements of type-1 quasars from Boroson et al (1985), Stockton & MacKenty (1987), and Husemann et al (2008Husemann et al ( , 2010. The continuum and line luminosities given in Stockton & MacKenty (1987) are converted to the values in the cosmology adopted here.…”
Section: Data Compilationmentioning
confidence: 99%
“…A direct decomposition the stellar continuum of the host galaxy underneath very luminous QSOs with deep optical IFU observations was previously attempted with VIMOS for HE 1029−1401 (Husemann et al 2010). Although HE 1029−1401 is much closer with a redshift of z = 0.086 but has a similar luminosity as PG 1307+085, the achieved S/N in the host spectrum was significantly lower than what we obtained with MUSE for PG 1307+085.…”
Section: The Bh Massσ * Relationcontrasting
confidence: 52%
“…Large reservoirs of ionized gas on tens to hundreds kpcs scales have been detected around many luminous radio-loud and radio-quiet AGN at low redshifts (Stockton & MacKenty 1983;Danziger et al 1984;van Breugel et al 1985;Stockton & MacKenty 1987;Prieto et al 1993;Shopbell et al 1999;Tadhunter et al 2000;Stockton et al 2002;Villar-Martín et al 2005Husemann et al 2010Husemann et al , 2011Greene et al 2012;Liu et al 2013aLiu et al , 2014Hainline et al 2014;Villar-Martín et al 2017 as well as at high redshifts (e.g. Heckman et al 1991;McCarthy 1993;Christensen et al 2006;North et al 2012;Cantalupo et al 2014;Hennawi et al 2015;Borisova et al 2016;Cai et al 2017;Arrigoni Battaia et al 2018;Husemann et al 2018).…”
Section: Introductionmentioning
confidence: 99%